Changes in leisure‐time physical activity and physical and mental health functioning: a follow‐up study. (7th October 2016) - Holstila, A.; Mänty, M.; Rahkonen, O.; Lahelma, E.; Lahti, J.
Abstract : Functioning will be an increasingly important issue in Finland over the coming decades as the proportion of the population aged 65 and older is growing significantly. However, the associations between changes in physical activity and subsequent health functioning are poorly understood. The aim of this study was to examine how changes in physical activity relate to concurrent and prospective levels of health functioning. Cohort data from the Helsinki Health Study were used. Phase 1 ( n  = 8960, response rate 67%, 80% women) was conducted among 40‐ to 60‐year‐old employees of the City of Helsinki in 2000–2002, phase 2 in 2007 ( n  = 7332, response rate 83%), and phase 3 in 2012 ( n  = 6814, response rate 79%). Linear mixed models were used as the main statistical method. Increasing physical activity was associated with higher concurrent and prospective levels of physical health functioning, whereas decreasing activity was associated with lower levels of physical health functioning. The associations were stronger with physical than with mental health functioning. Promoting physical activity among aging people may help to maintain their level of health functioning.